Response to the Lomagundi-Jatuli Event in the southwestern margin of the Yangtze Plate: Evidence from the carbon and oxygen isotopes of the Paleoproterozoic Yongjingshao Formation - Jun-ping Liu; Wei Yin; Shi-pan Yang; Jiang-tai Zhao; Wen-tao Zeng; Feng Tang; Shi-jun He; Wei-ke Li (China Geology, 2023)
The Lomagundi-Jatuli Event (LJE) refers to the significant positive carbon isotope excursion in seawater constituents that occurred immediately after the increase in atmospheric oxygen content during the Paleoproterozoic (2.22–2.06 Ga). The δ13C values of 46 dolostone samples collected from the Paleoproterozoic Yongjingshao Formation varied in the range of 0.05 ‰–4.95 ‰ (V-PDB; maximum: 4.95‰) in this study, which may be related to the multicellular eukaryotes in the Liangshan Formation in the Yimen Group. They are much higher than the δ13C values of marine carbonates (−1.16‰ on average). The δ13C values of other formations in the Paleoproterozoic Yimen Group are negative. The notable positive carbon isotope anomalies of the Yongjingshao Formation indicate the response to the LJE at the southwestern margin of the Yangtze Block, which is reported for the first time. Furthermore, they are comparable to the δ13C values of carbonates in the Dashiling Formation of the Hutuo Group in the Wutaishan area in the North China Craton, the Wuzhiling Formation of the Songshan Group in the Xiong’ er area, Henan Province, and the Dashiqiao Formation of the Liaohe Group in the Guanmenshan area, Liaoning Province. Therefore, it can be further concluded that the LJE is a global event. This study reveals that LJE occurred in Central Yunnan at 2.15–2.10 Ga, lasting for about 50 Ma. The macro-columnar, bean-shaped, and microfilament fossils and reticular ultramicrofossils of multicellular eukaryotes in this period were discovered in the Liangshan Formation of the Yimen Group. They are the direct cause for the LJE and are also the oldest paleontological fossils ever found. The major events successively occurring in the early stage of the Earth include the Great Oxygenation Event (first occurrence), the global Superior-type banded iron formations (BIFs), the Huronian glaciation, the Great Oxygenation Event (second occurrence), the explosion of multicellular eukaryotes, the positive carbon isotope excursion, and the global anoxic and selenium-rich sedimentary event. The authors think that the North China Craton and the Yangtze Craton were possibly in different tectonic locations of the same continental block during the Proterozoic.©2023 China Geology Editorial Office.